Prevalence of Addiction and Smoking and Their Relationship With Blood Parameters Among Drivers in Zahedan - Ansari-Moghaddam, Alireza (Int J High Risk Behav Addict, 2016)
BACKGROUND: Although smoking and drug use are the major causes of accidents and death of drivers, few studies have been conducted on the prevalence of smoking and its associated factors in this occupational group. OBJECTIVES: The current study aimed to investigate the prevalence of smoking and its relationship with blood parameters among drivers in Zahedan city, Iran. PATIENTS AND METHODS: In this study, 1836 inner and intercity drivers were investigated in 2013 in terms of smoking and drug use and blood parameters. Data were obtained through in-depth interviews and necessary examinations and tests, and were analyzed by Stata.12 software using Chi-square, independent t-test, and multiple regression analysis at significance level of 0.05. RESULTS: Generally, four drivers were addicted to drugs and smoked as well. Two-hundred and eighty eight drivers (15.8%) reported daily smoking. Variables of age, education, and type of vehicle showed a significant relationship with smoking. No significant difference was found in blood parameters between the smokers and non-smokers. CONCLUSIONS: Despite relatively high prevalence of smoking than drug use in Zahedan drivers, there are few reports of these behaviors. Laboratory tests cannot suitably measure substance use due to their interference with other substances. Considering adverse effects of smoking on health and driving, it is necessary to train drivers to reduce or stop smoking during driving.